On the Expanding Ludosphere. (June 2018) - Stenros, Jaakko; Kultima, Annakaisa
Background. Taking Klabbers' call for a coherent game science as a starting point, we argue for an alternative way to approach the multidisciplinarity of research into games. Aim. Building ongame studies anddesign research, this article reviews the history and forecasts the future of studying games. Application. All scholars of games could benefit from anawareness of the works of other game scholars in different traditions. The plurality of approaches towards games is an intellectual strength, even if it is difficult for a single scholar to maintain a holistic grasp on research relating to 'games'. The multitude not only describes the disciplinary traditions reflecting the wider phenomenon of games and play, but also games as creative practice. Demonstration. While the article is theoretical in nature, we use real-world examples to illustrate and ground the argumentation. For example, a key challenge identified here is that the realm of games and their influence, theludosphere, is expanding too rapidly for any single researcher to keep up with it. Conclusions. We invite game scholars to cultivate a stronger awareness of the multitude of research into games to better position their own work in a larger context.